2016
DOI: 10.1007/s00348-016-2186-9
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved and time-averaged stereo-PIV measurements of a unit-ratio cavity

Abstract: resulting in a significantly different cavity flow. Large turbulent sweep and ejection events in the wake flow suppress the typical shear layer and sporadic near wall sweep events generate coherent vortices at the upstream edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Figure 6 shows a wider range of turbulent intensity relative to the friction velocity u i /u τ for flows over street canyons of AR = 1:2 (d-type flows) compared with AR = 1:12 (k-type flows). Flows over both street canyons of AR = 1:2 and 1:12 exhibit more frequent events of sweep Q4 and ejection Q2, in line with the laboratory measurements over a single street canyon available in the literature [70]. For d-type flows over street canyons of AR = 1:2, P (u , w ) illustrates a similar shape over building roofs and street canyons such that stronger sweeps Q4 and ejection Q2 are more frequent than outward interaction Q1 and inward interaction Q3.…”
Section: Quadrant Analysissupporting
confidence: 86%
“…Figure 6 shows a wider range of turbulent intensity relative to the friction velocity u i /u τ for flows over street canyons of AR = 1:2 (d-type flows) compared with AR = 1:12 (k-type flows). Flows over both street canyons of AR = 1:2 and 1:12 exhibit more frequent events of sweep Q4 and ejection Q2, in line with the laboratory measurements over a single street canyon available in the literature [70]. For d-type flows over street canyons of AR = 1:2, P (u , w ) illustrates a similar shape over building roofs and street canyons such that stronger sweeps Q4 and ejection Q2 are more frequent than outward interaction Q1 and inward interaction Q3.…”
Section: Quadrant Analysissupporting
confidence: 86%
“…In order to show the influence of the choice of different scales and filter functions (parameters of the method) on the generated flow, simulations were performed on a turbulent boundary layer (see Section 3). The inflow statistics were derived from time resolved stereo-Particle Image Velocimetry (PIV) measurements [18].…”
Section: Turbulent Inflow Generationmentioning
confidence: 99%
“…The boundary layer measurements are reported in [18] and [16], where the boundary layer was measured upstream of a cavity. The boundary layer is not fully developed and therefore it is expected that the boundary layer will still further develop in flow direction in the LES simulations.…”
Section: Boundary Layer Simulationmentioning
confidence: 99%
“…Much effort has been done in recent years to analyze urban canopy flows by means of CFD, often using Reynolds-averaged NavierStokes (RANS) simulations of two-dimensional (2D) arrays of buildings. e interest of the scientific community for such a simplified building arrangement is justified by the fact that the 2D array can be considered as an archetype for more complex geometries [10][11][12][13]. Huang et al [14] carried out 2D simulations to investigate the effect of wedge-shaped roofs on the flow in an urban street canyon and found that they have significant influence on the vortex structure and pollutant distribution pattern.…”
Section: Introductionmentioning
confidence: 99%